RESPONS PERTUMBUHAN TUNAS JATI (Tectona grandis l.f) PADA BERBAGAI KONSENTRASI BAP DAN KINETIN SECARA IN VITRO - Muhammad, Fadel; Wulandari, Retno; Muslimin, Muslimin; Wahyuni, Dewi (Jurnal Warta Rimba, 2020)
Tectona grandis is an annual woody plant that has high economic value in trade commodities. Tectona grandis were usually produced in a conventional way using seed. However, large quantities of seed production in a given time become limited because of an outer layer of a hard seed. The success of tissue cultures is influenced by some factors, among which nutrients composition and plant growth regulator balance as a media component. Plant growth regulator which is used as a media component of tissue culture is the cytokinin Â and auksin. The aim of this research is to identify the concentration of kinetin and BAP (Benzyl Amino Purine) concentration is the best for Tectona grandis. The research was carried out for three months, from October to December 2019, located in The Biotechnology Laboratory of Agriculture, Faculty of Agriculture, Tadulako University, Palu. The research was utilizes completely randomized design, with 6 handling of BAP 1 mg, BAP 2 mg, BAP 3 mg, Kinetin 1 mg, Kinetin 2 mg dan Kinetin 3 mg. The result of observation shown giving handles BAP and Kinetin have a distinct effect on seedling Tectona grandis growth by in vitro. Besides the other treatment, kinetin 2 mg provides the best response that is emerge bud (5.1) of the day, the number of shoots (1.6) of shoots and the number of leaves (4) of sheets.Keywords: Tissue Culture, Tectona grandis, Kinetin